Production of lipopeptide biosurfactant by a hydrocarbon-degrading antarctic Rhodococcus - Abdul Habib, Nur Muhamad Syahir; Ahmad, Siti Aqlima; Wan Johari, Wan Lutfi; Abd. Shukor, Mohd Yunus; Yasid, Nur Adeela; Alias, Siti Aisyah; Smykla, Jerzy; Saruni, Nurul Hani; Abdul Razak, Nur Syafiqah (Multidisciplinary Digital Publishing Institute, 2020)
Rhodococci are renowned for their great metabolic repertoire partly because of their numerous putative pathways for large number of specialized metabolites such as biosurfactant. Screening and genome-based assessment for the capacity to produce surface-active molecules was conducted on Rhodococcus sp. ADL36, a diesel-degrading Antarctic bacterium. The strain showed a positive bacterial adhesion to hydrocarbon (BATH) assay, drop collapse test, oil displacement activity, microplate assay, maximal emulsification index at 45% and ability to reduce water surface tension to < 30 mN/m. The evaluation of the cell-free supernatant demonstrated its high stability across the temperature, pH and salinity gradient although no correlation was found between the surface and emulsification activity. Based on the positive relationship between the assessment of macromolecules content and infrared analysis, the extracted biosurfactant synthesized was classified as a lipopeptide. Prediction of the secondary metabolites in the non-ribosomal peptide synthetase (NRPS) clusters suggested the likelihood of the surface-active lipopeptide production in the strain’s genomic data. This is the third report of surface-active lipopeptide producers from this phylotype and the first from the polar region. The lipopeptide synthesized by ADL36 has the prospect to be an Antarctic remediation tool while furnishing a distinctive natural product for biotechnological application and research.